2021
DOI: 10.1097/pas.0000000000001778
|View full text |Cite
|
Sign up to set email alerts
|

HPV-negative Squamous Cell Carcinomas of the Cervix With Special Focus on Intraepithelial Precursor Lesions

Abstract: Recently, the World Health Organization (WHO) recognized human papilloma virus (HPV)-independent invasive cervical squamous cell carcinoma (SCC) without recognizing the existence of precursor lesions. This is a detailed characterization of 3 preinvasive lesions and 6 invasive SCC negative for HPV-DNA (32 genotypes), HPV-mRNA (14 genotypes) and genomic HPV sequencing. We evaluated histologic features, expression of p16ink4a, p53, CK7, and CK17, aberrations in 50 cancer genes and chromosomal copy number variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 33 publications
4
46
2
1
Order By: Relevance
“…Interestingly, a mutation in TP53 was not detected in case 5; however, immunohistochemistry for p53 demonstrated diffuse nuclear positivity, a finding which has previously been shown to be highly correlated with TP53 mutations 23. However, rare cases of an aberrant p53 staining pattern without TP53 mutations have been described 55. The significance of this finding is unclear.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, a mutation in TP53 was not detected in case 5; however, immunohistochemistry for p53 demonstrated diffuse nuclear positivity, a finding which has previously been shown to be highly correlated with TP53 mutations 23. However, rare cases of an aberrant p53 staining pattern without TP53 mutations have been described 55. The significance of this finding is unclear.…”
Section: Discussionmentioning
confidence: 88%
“…However, it was recently reported that two of three HPV-independent pre-invasive Review cervical lesions showed diffuse p16 ink4a staining, similar to the pattern shown in HPV-associated lesions. The authors excluded somatic or germline mutations in the RB gene or the CDKN2A gene encoding the p16 ink4a protein, 61 which could suggest the action of the 'hit-and-run' mechanism.…”
Section: Etiology Of Hpv-independent Tumorsmentioning
confidence: 99%
“…The authors of the review on human papillomavirus (HPV)-independent cervical cancer1 cited our recent publication on HPV-negative squamous precursor lesions2 as support for the ‘hit-and-run theory’ of primarily HPV-driven precancers that—during cancer progression—lose HPV-oncogene expression 3. Our data, however, were misinterpreted.…”
mentioning
confidence: 87%